Physical Activity Reduces the Prevalence of Periodontal Disease: Systematic Review and Meta-Analysis - Ferreira, Railson de Oliveira; Corrêa, Marcio Gonçalves; Magno, Marcela Baraúna; Almeida, Anna Paula Costa Ponte Sousa Carvalho; Fagundes, Nathália Carolina Fernandes; Rosing, Cassiano Kuchenbecker; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Physiology, 2019)
Background: Regular physical activity boosts several physical capacities and reduces many inflammatory markers of several diseases. In this sense, periodontal disease is a multifactorial inflammatory disease of tooth supporting tissues that has been claimed to trigger processes of systemic alterations. The aim of this systematic review and meta-analysis was to assess the effects of physical activity on periodontal disease. Methods: Observational studies published until August 2018 were searched in online databases (PubMed, Scopus, Web of Science, The Cochrane Library, LILACS, OpenGrey and Google Scholar) after developing a PECO statement that focused on the comparison between adults that followed a routine of exercises or presented a sedentary lifestyle and its effects on periodontal disease. Searching and data extraction were conducted by following PRISMA guidelines. Registration protocol: CRD42016049661. Quality assessment and risk of bias were analyzed by following Fowkes and Fulton protocol. Results: A total of 512 references were retrieved, while only seven were considered eligible. Two meta-analysis involving the prevalence of periodontal disease and unadjusted/adjusted Odds ratio were performed. One of studies did not find association between clinical periodontal parameters and physical activity. Six articles suggested an association between periodontal disease and regular practice of physical activity since a reduction of periodontal prevalence was observed. Moderate level of evidence was demonstrated on GRADE analysis. Conclusion: Physical activity was associated as a potential tool for reduction of periodontal disease prevalence. The frequency of physical activity is directly related to a low occurrence of periodontitis. However, it is important that further investigations evaluate the effects of other exercise variables, such as volume and intensity, on the periodontal disease prevalence.